Gout Arthritis During Admission for Decompensated Heart Failure—A Descriptive Analysis of Risk Factors, Treatment and Prognosis - Ritter, Fabian; Franzeck, Fabian; Geisshardt, Julian; Walker, Ulrich A.; Osthoff, Michael (Frontiers in Medicine, 2022)
Background Chronic heart failure and hospital admissions are well-known risk factors for acute gouty arthritis. However, in-depth analyses of patients admitted for decompensated heart failure (DHF) who subsequently developed a gout attack are sparse. This study aims to characterize DHF patients who developed a gout attack during their inpatient treatment and describe potential risk factors, its consequences, and its management in the setting of heart failure exacerbation. Methods Retrospective chart review of 50 patients with an admission diagnosis of DHF who subsequently experienced a gout attack during admission at a Swiss tertiary care hospital between 2018 and 2020. Patients with a refusal of the general research consent were excluded (n=10). Results A gout attack developed in 66/1832 (3.6%) DHF admissions of whom 50 individual patients were analysed. Patients were predominately male (76%), of advanced age (median 80.5 years), with several comorbidities including chronic kidney disease (74%), comorbid gout (70%, only 43% on urate lowering therapy) and hyperuricemia (median 547 µmol/l, IQR 434 – 667 µmol/l). Diuretics were intensified in all patients. Acute gout presented as polyarticular arthritis (62%) and was often accompanied by fever (30%). Joint aspiration was performed in 32%, and intra-articular steroid injections administered in 20% of patients. Median length of stay and 6-month mortality were 16 days (IQR 12 – 25) and 32%, respectively compared to 9 days (IQR 6 – 14) and 16% for DHF patients without a gout attack. Conclusion Our study highlights features of gout attacks in the context of DHF including the absence of comorbid gout in a significant proportion of patients, the presence of polyarticular disease during the flare, and a poor prognosis. The present study identifies the necessity to better address gout as a comorbidity in DHF patients and may assist clinicians in identifying DHF patients at risk for a gout attack.